2011
DOI: 10.1111/j.1741-4520.2010.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare clinical entity Perlman syndrome: Is cholestasis a new finding?

Abstract: Perlman syndrome is a rare syndrome characterized by polyhydramnios, fetal overgrowth, facial dysmorphism, visceromegaly, nephroblastomatosis and predisposition to Wilms tumor. Here we report on a newborn with a prenatal history of polyhydramnios who presented with nephromegaly, hypotonia, macrosomia, facial dysmorphism, cholestasis and characteristic ultrasonographic and computed tomographic appearances of renal abnormalities that are observed with Perlman syndrome. Perlman syndrome is a rare entity with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Prenatal suspicion and diagnosis is possible with the findings of macrosomia, polyhydramnios and renal anomalies or nephromegaly. 9 High neonatal mortality has been reported and >53% die within 28 days from birth. The high mortality has been linked to renal involvement and associated pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal suspicion and diagnosis is possible with the findings of macrosomia, polyhydramnios and renal anomalies or nephromegaly. 9 High neonatal mortality has been reported and >53% die within 28 days from birth. The high mortality has been linked to renal involvement and associated pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…By 2005 a total of 21 cases of Perlman syndrome were described [Piccione et al, ] and 3 years later Alessandri et al [] summarized the clinical features of 28 patients reported in the world literature.<QS>Perlman syndrome was recognized to be an autosomal recessively inherited condition. By 2005 a total of 21 cases of Perlman syndrome were described and 3 years later Alessandri et al summarized the clinical features of 28 patients reported in the world literature.</QS> Table provides a summary of the most common clinical features of Perlman syndrome (>50% of informative reports (presence or absence of features not available in all cases)) derived by combining the data presented by Alessandri et al [] with that from four further patients [Liban and Kozenitzky, ; Perlman et al, ; Neri et al, ; Greenberg et al, ; Henneveld et al, ; Alessandri et al, ; Demirel et al, ; Astuti et al, ]. In addition the frequency of the findings in the subset of patients known to have DIS3L2 mutations is recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Rh ve ABO izoimmünizasyonunda İVİG ile tedavinin etkinliğini inceleyen çalışmalar değerlendirildiğinde, İVİG tedavisinin kan değişimi sıklığını azalttığı bildiren yayınlar yanında (13) kan değişimi, eritrosit süspansiyonu gereksinimi ve hastanede yatış süresi üzerinde etkisi olmadığını bildiren yayınların da mevcut olduğu görülmektedir (14). Etki mekanizması tam bilinmemekle birlikte Fc reseptörüne bağlanan immunglobulinlerin retüküloendotelyal sistem aracılığı ile gerçekleşen eritrosit yıkımını engellediği düşünülmektedir (7).…”
unclassified